Pengaruh Perilaku Berdagang Terhadap Keuntungan Penjualan Pada Pedagang Sembako Di Pasar Tradisional Pabuaran Subang - Seliwati Seliwati (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
After the global economic crisis since 2008 many economic experts from various countries, especially in the West. Looking for alternative economic concepts that are more established to be implemented in order to get out of the global economic crisis. One alternative is the concept of Islamic economics or Islamic economics which is currently in great demand. With so many delinquency cases of business people or business, Islamic business ethics is very reference to business people so that they do not do too much delinquency in their many previous businesses. Lately, the rules of Islamic business ethics have quickly become the spotlight of various circles for his efforts to be more blessed, to develop according to the Shari'a without cheating in obtaining business profits, especially among medium-sized Islamic business ethics. The research formulation in this thesis is: (1) is there an effect of trading behavior on the profit of the sale of the basic needs traders with the ethical study of Islamic business? (2) how big is the effect of trading behavior on sales profits on basic food merchants with the study of Islamic business ethics? The purpose of this study was to determine the effect of merchant behavior on the profit of sales at the sembako merchants in the traditional Pabuaran market with the study of Islamic business ethics, and to find out the magnitude of the effect of trading behavior on the profit of sales at sembako merchants in the traditional Pabuaran market based on the study of Islamic business ethics. The method used in this research is quantitative descriptive. Analysis of the data using normality, validity, reliability and linearity test, t and Rsquare test processing the data using SPSS 22 for windows. With the results obtained in this study the level of influence of variable X on variable Y, from the results of Rsquare values ​​the effect of independent variables (trading behavior) on the dependent variable (sales profit) of 48,9%, while the remaining 51,1% is determined by the influence of factors others that were not explained in this study. Based on the results of research and discussion of research it can be concluded that profits are influenced by the trading behavior of each trader. From the results of research, traders in Pabuaran Market have implemented Islamic business ethics with every trade transaction without selling defective or defective items that are not suitable for sale, do not reduce the scale or exaggerate but are adjusted to the needs of the buyer, fair in providing services that do not differentiate - the difference between buyers is still valid honest and friendly.